2000
DOI: 10.1111/j.1945-5100.2000.tb01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Space weathering on airless bodies: Resolving a mystery with lunar samples

Abstract: Abstract— Using new techniques to examine the products of space weathering of lunar soils, we demonstrate that nanophase reduced iron (npFe0) is produced on the surface of grains by a combination of vapor deposition and irradiation effects. The optical properties of soils (both measured and modeled) are shown to be highly dependent on the cumulative amount of npFe0, which varies with different starting materials and the energetics of different parts of the solar system. The measured properties of intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
416
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 577 publications
(430 citation statements)
references
References 34 publications
11
416
1
2
Order By: Relevance
“…4 Telescopic spectrum of Vesta (circles) compared to laboratory spectra of different particle size separates for the howardite EET87503 (after Hiroi et al 1994) cal rocks? After decades of study, a principal cause (but not the precise origin) of the optical properties of lunar space weathering is now understood to be the development and accumulation of nanophase metallic iron, npFe 0 , on soil particles (Pieters et al 2000;Hapke 2001). A similar accumulation of nanophase opaque particles appears to be operative to a lesser extent on some chondritic asteroid surfaces altering the surface to what is now observed as an abundant class of "S-type" asteroids.…”
Section: Three Case Study Science Themes At Vestamentioning
confidence: 99%
See 1 more Smart Citation
“…4 Telescopic spectrum of Vesta (circles) compared to laboratory spectra of different particle size separates for the howardite EET87503 (after Hiroi et al 1994) cal rocks? After decades of study, a principal cause (but not the precise origin) of the optical properties of lunar space weathering is now understood to be the development and accumulation of nanophase metallic iron, npFe 0 , on soil particles (Pieters et al 2000;Hapke 2001). A similar accumulation of nanophase opaque particles appears to be operative to a lesser extent on some chondritic asteroid surfaces altering the surface to what is now observed as an abundant class of "S-type" asteroids.…”
Section: Three Case Study Science Themes At Vestamentioning
confidence: 99%
“…Lunar soils were darker, absorption bands were greatly subdued, and the overall shape of the continuum was also altered. Decades later, when detailed analyses with modern equipment identified nanophase metallic iron (npFe 0 ) that had accumulated on the surface of lunar grains, it was recognized that these nanophase opaque particles are the principal cause of much of the observed optical properties of lunar soils McKay 1993, 1997;Pieters et al 2000;Noble et al 2001Noble et al , 2007. Meteorite regolith breccias, as proxies for asteroidal regolith, were searched for similar nanophase particles, with the howardite Kapoeta being one of the few minor, but successful detections (Noble et al 2010).…”
Section: Spwe: Backgroundmentioning
confidence: 99%
“…Lucey and Noble [2008] suggested that iron particles in this size regime be termed "microphase iron" or "Britt-Pieters particles", after the work of Britt and Pieters [1994] on shock darkening of chondritic meteorites. Finer-grained metal, less than $50 nm in diameter, is referred to as "nanophase iron" (npFe 0 ) and produces decreased reflectance while introducing a strong positive spectral slope across the visible to near-infrared (i.e., spectral "reddening") [Pieters et al, 2000;Noble et al, 2007]. Nanophase iron metal in particular is relevant for unraveling space weathering effects, which are dramatically apparent in laboratory spectra of returned lunar samples.…”
Section: Introductionmentioning
confidence: 99%
“…Opaque iron metal and its various alloys are often found as native igneous minerals in meteorites and on planetary surfaces in the form of grains significantly larger than the wavelength of the incident light. However, nanophase iron metal grains are also a key by-product of space weathering [Keller and McKay, 1997;Pieters et al, 2000;Hapke, 2001;Noble et al, 2007] and introduce confounding effects on ultraviolet (UV), visible (VIS), and near-infrared (NIR) spectra as seen in laboratory and spacecraft data for airless bodies (e.g., Clementine, Moon Mineralogy Mapper (M 3 ), Lunar Reconnaissance Orbiter (LRO) Wide-Angle Camera (WAC), Dawn, Hayabusa, and MESSENGER). Sufficient knowledge of the optical properties of these metals is necessary for effective spectral characterization and theoretical modeling analysis of mixtures containing these constituents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation